The function of the educational value in the ma’parapa (silence) text in the process of the rampanan kapa’ (wedding ceremony) - Harmita Sari; Andi Rizkiyah Hasbi; Sukmawati Tono Palangngan (Faculty of Social and Political Science, Universitas Airlangga, 2020)
One community that has a complex marriage system is Toraja, it is one of the tribes in Indonesia who still maintains their ancestral cultural traditions in their social life. The institutions in the Toraja communities are always associated with aluk (teachings or rules of life). This study aims to describe the educational values and functions in the text ma’parapa (silence) in the procession of rampanan kapa’ (wedding ceremony) in Tana Toraja. This type of research is qualitative research, and the research data is in the form of text quotations that describe the educational value contained in the ma’parapa text in the procession of the rampanan kapa’ in Tana Toraja. The results of this study indicate that the educational value contained in the text ma’parapa in the procession of rampanan kapa’ consists of 1) the value of religious education, namely to educate all people always to be grateful, to trust, and to exalt God’s power, 2) moral education, namely to express respect or in the sense of asking for permission before doing something in front of others by saying the word tabe, 3) social education, which is useful for the community to foster life with its environment, 4) cultural education, namely inviting all people to always maintain and develop marriage customs in it there are procedures for getting married which contain many moral messages that need to be applied in everyday life. The educational function of the ma’parapa text in the procession of rampanan kapa’ in Tana Toraja includes 1) the function of education for family and cultural groups, which is to encourage the younger generation to dare to speak in public, to be able to implement good behavior in daily life -day, and so that the younger generation can interpret advice, and relationships with God Almighty, and 2) to understand aluk rampanan kapa’ as a very sacred level of the ceremony where if there is a violation it will be sanctioned by fellow humans and also from the Creator.